De Novo Interstitial Microdeletion at 1q32.1 in a 10-Year-Old Boy with Developmental Delay and Dysmorphism. (3rd February 2016) - Carter, Jennifer; Zombor, Melinda; Máté, Adrienn; Sztriha, László; Waters, Jonathan J.
Abstract : A 10-year-old boy was referred with developmental delay and dysmorphism. Genomewide aCGH microarray analysis detected a de novo 3.7 Mb deletion at 1q32.1: arr 1q32.1(199, 985, 888-203, 690, 832)x1 dn [build HG19]. This first report of a deletion in this region implies a critical role for dosage-sensitive genes within 1q32.1 in neurological development. This is consistent with previously reported duplications of this region in patients with a similar phenotype.